FEM analysis of dynamic behavior of asphalt pavement structure weakened by grassroots with account of hydraulic and vehicle load coupling effects. Issue 1 (November 2015) - Huang, J; Pan, X; Dai, S B; Cai, Y
Abstract: This paper establishes the finite element model of saturated asphalt pavement with ANSYS. The thickness and elastic modulus of pavement surface layers and grassroots are taken as influencing factors to analyze the influence of these factors' change on the pavement mechanical behavior. The results indicate that the increase of surface thickness leads to the shear stress's decrease that may relieve the internal shear stress concentrated phenomenon effectively. The increase of elastic modulus of surface makes the pore pressure decrease, and result in the shear stress's increase. The grassroots thickness has no obvious effect on the pore- water pressure and shear stress; the grassroots elastic modulus' increase may increase the internal shear stress and decrease the pore pressure.